RANBooster: Democratizing advanced cellular connectivity through fronthaul middleboxes - Foukas, Xenofon; Ukyab, Tenzin Samten; Radunovic, Bozidar; Ratnasamy, Sylvia; Shenker, Scott (SIGCOMM 2025, 2025)
The 5G Radio Access Network has shifted towards virtualization and disaggregation. This change aims to reduce costs and foster innovation by promoting vendor interoperability and by expanding the ecosystem. In this environment, smaller RAN vendors and open-source projects have emerged, focusing on low-cost, modular stacks. However, challenges such as achieving state-of-the-art performance and accessing data and control knobs hinder their widespread adoption. To address these issues, we propose a middlebox architecture, called RANBooster, that enhances the RAN capabilities without modifying existing network functions, by leveraging the open fronthaul interface. To demonstrate the benefits of the RANBooster framework, we build four reference applications (distributed antenna system, distributed MIMO, RU sharing, real time physical resource block monitoring), and evaluate them on an enterprise-scale, commercial-grade 5G testbed.